Surface morphology and wettability of sandblasted PEEK and its composites. Issue 1 (3rd April 2013) - Ourahmoune, R.; Salvia, M.; Mathia, T.G.; Mesrati, N.; Brown, Christopher A.
Summary PolyEtherEtherKetone (PEEK) is an advanced high‐performance thermoplastic polymer, and its composites are used extensively in the aeronautical industry. This paper presents an experimental approach to determine the role of sandblasting treatment on surface morphology modifications of PEEK and its composites, with the aim of developing a topographic characterization in order to propose pertinent parameters that correlate with contact angles from wettability measurement. Sandblasting (fine abrasive particle projection) was selected as the surface treatment, in order to obtain various morphologically quasi‐isotropic surfaces. Two surface metrological approaches to topographical characterization were used to correlate the wettability behavior with the surface roughness parameters, the first based on 2D profile analysis and the second on 3D topography analysis. Two different unreinforced grades of PEEK and four composites: discontinuous carbon fiber or glass fiber‐reinforced, oriented, and unoriented, were studied. The experimental results indicated the sandblasting process duration necessary to reach a morphological steady state. It was stated that one of the pertinent parameters is the mean slope of roughness motif in 2D profile characterization, as confirmed by previous findings for anisotropic morphologies. However, for all cases, a new topographic parameter Sr, combining the surface amplitude and the summit density distribution, is proposed as a factor well‐correlated with wettability characteristics. SCANNING 36:64–75, 2014. © 2013 Wiley Periodicals, Inc.